The ecology of vascular epiphytes in the Peruvian Andes - Heathcote, S (2013)
Little is known about the composition of tropical epiphytic communities and the influence of environmental variables on community composition. In this thesis I quantify the diversity and biomass of bromeliads, and other vascular epiphytes along an altitudinal transect on the eastern slope of the southeast Peruvian Andes and then look for species’ adaptations related to patterns of diversity and biomass. I compare patterns with those of woody species. Bromeliad species, like tree species, were found to form ecological zones related to climate. The lowest altitude ecological zone (below 1250 m) is the lowland rainforest (LRF), which has the warmest climate and highest evapotranspiration. In LRF vascular epiphytes are less prominent than other ecological zones, with the lowest bromeliad species richness and lowest vascular epiphyte biomass. However, low water-availability gives rise to most variable shoot morphology of bromeliads. The tropical montane forest (TMF), between 1250 m and 2250 m, is intermediate in climate between the LRF and the tropical montane cloud forest (TCF). The TMF has the highest α-diversity, but species richness is lower than the TCF. The shoot morphology of bromeliads is intermediate between TCF and LRF. The highest altitude ecological zone with forest is the TCF (above 2250 m). The TCF has the highest bromeliad species richness, and lowest diversity of shoot forms. The low diversity of shoot forms represents the need for a large phytotelm (water-impounding shoot) to intercept and store precipitation. The TCF has the highest vascular epiphyte biomass, although the biomass is variable as a consequence of the natural disturbance caused by landslides. Along the transect bromeliad species with CAM photosynthesis are only present in the LRF. Terrestrial bromeliad distribution records covering the Neotropics show CAM photosynthesis is more prevalent in drier environments showing that CAM photosynthesis is primarily an adaptation to drought. Epiphytic bromeliads, pre-adapted to a water-stressed environment show no differences in presence along rainfall gradients, but species with CAM photosynthesis occupy warmer environments.